2020
DOI: 10.1155/2020/1346045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Immune-Related Genes in Pancreatic Adenocarcinoma and Establishment of a Prognostic Nomogram: A Bioinformatic Study

Abstract: Background. The prognosis of pancreatic adenocarcinoma (PAAD) is extremely poor and has not been improved. Thus, an effective method to assess the prognosis of patients must be established to improve their survival rate. Method. This study investigated immune-related genes that could be used as potential therapeutic targets for PAAD. Level 3 gene expression data from the PAAD cohort and the relevant clinical information were obtained from The Cancer Genome Atlas (TCGA) database. For validation, other PAAD data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…37 Moreover, the expression of CD1D, ERAP2, SSTR1, CXCL9, CXCL11, IL1A, EREG also certainly influenced the development of PC. [38][39][40][41][42][43][44][45][46] Hence, these studies demonstrated the correlation between our IRGPs signature with the progression of PC.…”
Section: Discussionsupporting
confidence: 68%
“…37 Moreover, the expression of CD1D, ERAP2, SSTR1, CXCL9, CXCL11, IL1A, EREG also certainly influenced the development of PC. [38][39][40][41][42][43][44][45][46] Hence, these studies demonstrated the correlation between our IRGPs signature with the progression of PC.…”
Section: Discussionsupporting
confidence: 68%
“…Chung et al [35] reported the prognostic value of serum fibrinogen to PAAD patients; serum fibrinogen expression was significantly higher in patients with distant metastasis, and the median OS was longer in patients with lower serum fibrinogen levels. Wu et al [36] identified three immune-related genes (CKLF, ERAP2, and EREG) and determined the prognostic signature of PAAD patients. Patients with high-risk scores were associated with a poor prognosis, with AUC values of 0.612 to 0.687.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated analysis of relationships between immune-related genes and clinical outcomes of pancreatic cancer is critical to explore novel prognostic markers as well as therapeutic targets. For example, Wu et al found that three immune-related genes CKLF, ERAP2, and EREG showed distinct correlations with pancreatic cancer patients' survival ( 11 ). In this study, we identified three immune-related prognostic genes MET, OAS1, and OASL from the 21-gene signature.…”
Section: Introductionmentioning
confidence: 99%